Large Area Patterned Magnetic Films by Depositing Cobalt Layers on Nano-Wrinkled Polydimethylsiloxane Templates - Melo-Hurtado, F; Caballero-Alvial, L; Cerda-Villablanca, E; Casagrande-Denardin, J; Briones, J (2013)
We report on a method to fabricate laterally modulated Co films using the artificially induced nano-wrinkled surface of a polydimethylsiloxane polymeric film as template. Large area patterning of self-organized parallel wrinkles is formed displaying a submicrometer wavelength. The subsequent deposition of a Co layer on this wavy surface yields a uniaxial magnetic anisotropy imposed by the wrinkles morphology. Measurement of the remanent magnetization and coercive field as a function of the field angle confirms the uniaxial nature of the anisotropy and reveals a reversal mechanism more complex than pure coherent rotation. The magnetostatic origin of the anisotropy is analyzed. © 2013 AIP Publishing LLC.